EVALUASI PERENCANAAN ANGGARAN BELANJA DI MADRASAH - Hidayat, Taufik; Khuriyah, Khuriyah (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2025)
This research is a research in examining the budget planning in Islamic educational institutions, both from the policy level (government) to the implementation in Madrasahs. This research will later find an overview and solution to the problem of planning the education expenditure budget in madrasas. This research aims to find out how the planning, implementation, supervision, and evaluation of the Islamic education expenditure budget in Indonesia is planned. The research method used is descriptive research with a qualitative approach. Data collection techniques are carried out through observation, interviews, and documentation, with data analysis through data reduction, data presentation, and conclusion drawn. The results of the study revealed that: Budget planning through the preparation of the Madrasah Budget Work Plan involves needs analysis, expenditure planning, and consultation with the head of the madrasah, treasurer, administration, teacher council, and committee, Madrasah Budget Work Plan helps estimate expenditure needs for one school year, Implementation Expenditure includes the expenditure of funds from four sources, namely School Operational Cost funds as the main source, committees, madrasah businesses and other sources used for operational and sudden needs, Supervision is carried out by internal and external parties to ensure the budget is as planned. Evaluations are carried out every three months by the head of the madrasah to ensure the use of the budget in accordance with the Madrasah Budget Work Plan. ABSTRAKPenelitian ini merupakan penelitian dalam mengkaji perencanaan anggaran belanja yang ada di lembaga pendidikan Islam, baik dari tingkat kebijakan (pemerintah) hingga kepada pelaksanaan di Madrasah. Penelitian ini nantinya akan menemukan sebuah gambaran dan solusi terhadap permasalahan perencanaan anggaran belanja pendidikan di madrasah. Penelitian ini bertujuan untuk mengetahui bagaimana perencanaan, pelaksanaan, pengawasan, serta evaluasi anggaran belanja pendidikan Islam di Indonesia. Metode penelitian yang digunakan adalah penelitian deskriptif dengan pendekatan kualitatif. Teknik pengumpulan data dilakukan melalui observasi, wawancara, dan dokumentasi, dengan analisis data melalui reduksi data, penyajian data, dan penarikan kesimpulan. Hasil penelitian mengungkapkan bahwa : Perencanaan anggaran melalui penyusunan Rencana Kerja Anggaran Madrasah melibatkan analisis kebutuhan, perencanaan pengeluaran, dan konsultasi dengan kepala madrasah, bendahara, tata usaha, dewan guru, dan komite, Rencana Kerja Anggaran Madrasah membantu memperkirakan kebutuhan belanja untuk satu tahun ajaran, Pelaksanaan belanja mencakup pengeluaran dana dari empat sumber yaitu dana Biaya Operasional Sekolah sebagai sumber utama, komite, usaha madrasah dan sumber lain digunakan untuk kebutuhan operasional dan mendadak, Pengawasan dilakukan oleh pihak internal dan eksternal untuk memastikan anggaran sesuai rencana. Evaluasi dilakukan setiap tiga bulan oleh kepala madrasah untuk memastikan penggunaan anggaran sesuai Rencana Kerja Anggaran Madrasah.